2003
DOI: 10.1557/jmr.2003.0072
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of BaSn(OH)6 and BaSnO3 acicular particles

Abstract: The synthesis of BaSn(OH)6 acicular crystals by precipitation at 100 °C from aqueous solutions and their transformation in the perovskitelike compound BaSnO3 was investigated. Single acicular crystals 100–200 μm in length were obtained from a 0.05M solution, whereas bundlelike aggregates of 20–40 μm were precipitated from 0.2–0.6 M solutions. The x-ray diffraction pattern of barium hexahydroxostannate was indexed according to monoclinic symmetry with cell parameters a = 11.029 ± 0.002 Å, b = 6.340 ± 0.001 Å, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…In the last few years many preparation procedures have been reported to obtain fine-grained BaSnO 3 powders at relatively low temperatures. Different hydrothermal methods or sol-gel processes have been developed and reported in literatures [15][16][17][18][19][20]. Recently, a lyothermal synthesis at 250 • C has been reported by Lu and Schmidt [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years many preparation procedures have been reported to obtain fine-grained BaSnO 3 powders at relatively low temperatures. Different hydrothermal methods or sol-gel processes have been developed and reported in literatures [15][16][17][18][19][20]. Recently, a lyothermal synthesis at 250 • C has been reported by Lu and Schmidt [21].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of carbonates has been reported even at a calcination temperature of 1000°C during the synthesis of SrSnO 3 and BaSnO 3 by polymeric complex method (Udawatte et al 2000). In hydrothermal synthesis of these stannates (Buscaglia et al 2003;Lu and Schmidt 2005) at low temperature, the product contains OH -ions in lattice even at a calcination temperature of 1200°C.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen a thermal treatment above 1000 • C leads to parameters which do not significantly change with increasing temperature. Buscaglia et al 23 investigated the decomposition of BaSn(OH) 6 to BaSnO 3 and observed a decreasing cell parameter with increasing annealing temperature, too. By Raman spectroscopy they found that the powders, calcined at very low temperatures, retain a lot of hydroxyl groups inside the lattice, which cause the larger cell parameter.…”
Section: Powder Characterisationmentioning
confidence: 99%
“…[19][20][21][22][23] A peroxide method was reported by Pfaff 24 to synthesise phase pure BaSnO 3 . Recently, a lyothermal synthesis at 250 • C has been reported by Lu and Schmidt.…”
Section: Introductionmentioning
confidence: 99%